Tick saliva inhibits dendritic cell migration, maturation, and function while promoting development of Th2 responses - Fialová, Anna; Iezzi, Giandomenica; Ampenberger, Franziska; Kopf, Manfred; Kopecký, Jan (The Journal of immunology, 2008)
Similarly to other blood-feeding arthropods, ticks have evolved immunosuppressive mechanisms enabling them to overcome the host immune system. Although the immunomodulatory effect of tick saliva on several cell populations of the immune system has been extensively studied, little is known about its impact on dendritic cells (DCs). We have examined the effect of Ixodes ricinus tick saliva on DC function in vitro and in vivo. Exposure of DCs to tick saliva in vitro resulted in impaired maturation, upon CD40 or TLR9, TLR3 and TLR7 ligation, as well as reduced Ag presentation capacity. Administration of tick saliva in vivo significantly inhibited maturation and early migration of DCs from inflamed skin to draining lymph nodes, and decreased the capacity of lymph node DCs to present soluble Ag to specific T cells. Moreover, saliva-exposed DCs failed to induce efficient Th1 and Th17 polarization and promoted development of Th2 responses. Our data reveal a complex inhibitory effect exerted by tick saliva on DC function. Given the role of DCs as the key instigators of adaptive immune responses, alteration of their function might represent a major mechanism of tick-mediated immune evasion.
Keywords: CD40 Antigens; Th1 buňky; Saliva; Financing, Organized; financování organizované; Th2 buňky; sliny; toll-like receptory; lymfatické uzliny; imunologická tolerance; Toll-Like Receptors; prezentace antigenu; klíště; antigeny CD40; myši; Mice; Immune Tolerance; Ixodes; Th1 Cells; Cell Movement; Th2 Cells; Antigen Presentation; zvířata; pohyb buněk; Lymph Nodes; Dendritic Cells; Animals; dendritické buňky